Social Networking Services in E-Learning - Weber, Peter; Rothe, Hannes (Proceedings of World Conference on E-Learning in Corporate, Government, Healthcare, and Higher Education (E-LEARN) 2012, 2012)
This paper is a report on the findings of a study conducted on the use of the social networking service NING in a cross-location e-learning setting named “Net Economy”. We describe how we implemented NING as a fundamental part of the setting through a special phase concept and team building approach. With the help of user statistics, we examine the value of the implemented social networking service with regard to the need for a social presence, as emphasized by the Community of Inquiry framework. Findings indicate that NING led to a well-meshed network of relationships among the students from the participating locations and that the development of these relationships was fundamentally influenced by the chosen phase concept and team building approach. Further, we show that with the help of social networking services, interconnections between students in virtual teams become more transparent and can be influenced systematically.
Keywords: Community of Inquiry Framework; E-Learning; Social Network Analysis; Social Networking Services